Friedrich Paul Magerl - "ORTHOPAEDICS, TRAUMATOLOGY; PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
On November 14, 2020, Professor Dr. Friedrich Paul Magerl, a pioneer in spinal surgery and orthopedics, passed away.